(untitled) (Research, Society and Development, 2022)
Introduction: The studies on the consequences of noise to the auditory system are well documented, particularly in workers’ health. Nevertheless, few studies in the field yet have related postural control to occupational noise exposure. Objective: To investigate the association between the history of occupational noise and the postural control in older adults. Materials and Methods: Cross-sectional study that included individuals of both sexes older than 60 years. All of them had their postural control assessed on a force platform. The occupational noise was assessed with an audiological anamnesis questionnaire. The hearing loss was assessed using the pure-tone threshold audiometry. The Tinnitus Handicap Inventory questionnaire was used to quantify the impact of tinnitus on daily life of the older adults. Results: 90 older adults (87.8% women, 70[64-75] years old) were analyzed. The history of occupational noise exposure was associated with a worse postural control in older adults, regardless of the person’s age (ANCOVA; P < 0.05). Moreover, the greater the hearing loss, the greater the body instability of the older adults (r≤0.36 for all). Finally, postural control was related to tinnitus presenting correlations with catastrophic Tinnitus Handicap Inventory (r = 0.314; P = 0.038) and functional Tinnitus Handicap Inventory (r = 0.430; P = 0.010). Conclusion: Postural control of older adults is related to the history of occupational noise exposure, hearing loss and tinnitus impact on older adult’s daily life.